(untitled) (Bioresearch Communications, 2024)
Labeo rohita, commonly known as rui/rohu possesses an important role in agricultural and economic aspects in Bangladesh. This study aimed to characterize the mitochondrial genome of this economically important fish species. Primers (24 pairs) were designed to amplify the whole genome and most of the regions contained 700 to 800bp. In this study, nucleotide sequences of 16,607 bp of the mitochondrial genome of L. rohita were determined for the first time from Bangladesh, which consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and one D-loop region. All of the genes were similar in size compared to other fish mitochondrial genomes. The gene arrangements, and intergenic and gene overlapping nucleotides of the present study, were similar to that of other Labeo genera so far reported. The phylogenetic tree shows 100% similarity in L. rohita mitochondrial genomes collected from two different areas of Bangladesh. This nucleotide sequence data of the mitogenome of L. rohita would provide necessary information for further studies, including population genetics of carp fishes. Bioresearch Commu. 10(2): 1539-1544, 2024 (July)